Intergenerational spillovers: The impact of labor market risk on the housing market - Leanne Jae Youn Nam (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Unemployment leads to large and persistent income losses for workers. Higher unemployment in the labor market therefore has spillover effects on the housing market. This paper studies such spillover effects from both empirical and theoretical perspectives. Using data from the Current Population Survey (CPS), I show that a 1 percentage point increase in unemployment rate leads to a 1.55% decline in housing prices. Theoretically, I develop an overlapping generations model with a housing market. The calibrated model replicates the empirically observed spillover effect for the U.S. economy. Higher income uncertainty is the main driver of the spillover effect, rather than actual income losses. The spillover effect transmits one-third of the welfare losses of workers due to higher unemployment in the labor market to older, retired households by reducing their housing wealth. Younger workers benefit in part by buying houses at depressed prices. The magnitude of the spillover effect is shaped by the demographic structure of the population and the specific age groups affected by unemployment shocks. I find that increasing the generosity of unemployment insurance stabilizes the housing market, although it only partially mitigates the spillover effect.
Keywords: G11; R21; E21; E24; 330; Unemployment; Housing demand; Portfolio choice; Overlapping generations